The Response Regulator YycF Inhibits Expression of the Fatty Acid Biosynthesis Repressor FabT in Streptococcus pneumoniae - Mohedano, Maria L.; Amblar, Mónica; de la Fuente, Alicia; Wells, Jerry M.; López, Paloma (Frontiers in Microbiology, 2016)
The YycFG (also known as WalRK, VicRK, MicAB or TCS02) two-component system (TCS) is highly conserved among Gram-positive bacteria with a low G+C content. In Streptococcus pneumoniae the YycF response regulator has been reported to be essential due to its control of pcsB gene expression. Previously we showed that overexpression of yycF in S. pneumoniae TIGR4 altered the transcription of genes involved in cell wall metabolism and fatty acid biosynthesis, giving rise to anomalous cell division and increased chain length of membrane fatty acids. Here, we have overexpressed the yycFG system in TIGR4 wild-type strain and yycF in a TIGR4 mutant depleted of YycG, and analyzed their effects on expression of proteins involved in fatty acid biosynthesis during activation of the TCS. We demonstrate that transcription of the fab genes and levels of their products were only altered in the YycF overexpressing strain, indicating that the unphosphorylated form of YycF is involved in the regulation of fatty acid biosynthesis. In addition, DNA-binding assays and in vitro transcription experiments with purified YycF and the promoter region of the FabTH-acp operon support a direct inhibition of transcription of the FabT repressor by YycF, thus confirming the role of the unphosphorylated form in transcriptional regulation.